1987
DOI: 10.1159/000234197
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mast Cells in Inflammatory Processes: Evidence for Nerve/Mast Cell Interactions

Abstract: In the rat, there is considerable evidence of mast cell/nerve interaction both in the normal and infected intestine. Between 67 and 87% of all mast cells in the intestinal lamina propria of rats infected 22–35 days earlier with Nippostrongylus brasiliensis were touching nerves. These membrane contacts were between subepithelial mast cells and nonmyelinated nerves containing substance P, calcitonin gene-related peptide and neurone specific enolase. 2.5S nerve growth factor (NGF) has a significant enhancement ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
73
0
5

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(84 citation statements)
references
References 22 publications
6
73
0
5
Order By: Relevance
“…B-and T-cell number and distribution in spleen, thymus, bone marrow and blood appear unaffected by TrkA deletion. Similar results have been obtained for mast cells in skin, spleen and lymph nodes despite reports that NGF injections cause their increase in various tissues of neonatal rats (Aloe and Levi-Montalcini, 1977;Bienenstock et al, 1987;Bullock and Johnson, Jr, 1996). This is a striking result because many studies suggested that disruption of the NGF/TrkA system in the immune system would cause dramatic deficits.…”
Section: Discussionsupporting
confidence: 81%
“…B-and T-cell number and distribution in spleen, thymus, bone marrow and blood appear unaffected by TrkA deletion. Similar results have been obtained for mast cells in skin, spleen and lymph nodes despite reports that NGF injections cause their increase in various tissues of neonatal rats (Aloe and Levi-Montalcini, 1977;Bienenstock et al, 1987;Bullock and Johnson, Jr, 1996). This is a striking result because many studies suggested that disruption of the NGF/TrkA system in the immune system would cause dramatic deficits.…”
Section: Discussionsupporting
confidence: 81%
“…Basophil/mast cell and eosinophil differentiation-promoting factors are produced by human nasal polyp and allergic rhinitis mucosal epithelial scrapings in vitro, suggesting the importance of locally derived factors in the regulation of numbers of these specialized granulocytes in allergic inflammation (17,18). We have also shown extensive mast cell/nerve structural membranemembrane associations in normal and inflamed rat intestines (9,10). Mast cell/nerve interactions may be important in various forms of neurogenic inflammation, in vivo and in the homeostatic regulation of various internal physiologic parameters (19)(20)(21)(22).…”
mentioning
confidence: 59%
“…NGF is secreted by fibroblasts (46) and can induce in dose-dependent manner significant increases in mast cell numbers of both mucosal and connective tissue type, according to their normal predominance in a particular tissue, after injection into neonatal rats (8,9). Since NGF can also promote the effect of T-cellderived lymphokines or induce T cells to secrete CSA, NGF may play a significant role in both inflammation and tissue repair, as has already been suggested in wound-healing experiments (2,7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mast cells are involved in inflammatory and hypersensitivity reactions (1) and occur in many peripheral tissues, in perivascular regions in close apposition to innervating sensory or autonomic nerve fibers (2), and also within the peripheral and central nervous systems (3). Nervous and immunological mediators such as neuropeptides or IgE can affect the state of mast cell activation (4).…”
mentioning
confidence: 99%